PTH-332 Pre-operative inflammatory cell ratios (NLR and PLR) predict post-operative complications and poor outcomes following surgery for rectal cancer. (22nd June 2015) - Egan, RJ; Jones, HG; Radwan, R; Davies, M; Evans, M; Beynon, J; Harris, DA
Abstract : Introduction: Elevated post-operative inflammatory ratios have been associated with complications following colorectal surgery, and a reduction in cancer specific survival. 1, 2 No studies have previously evaluated the value of pre-operative inflammatory ratios in predicting post-operative complications Method: Consecutive rectal cancer resections in a tertiary referral centre were evaluated using prospectively maintained clinical databases, and review of clinical notes if required. Patients with post-operative septic complications (n = 54; 17=anastomotic leak; 13=flap/perineal wound complication; 21=pelvic collection; 3=wound complication/other) were compared to those with no such complications (controls; n = 161). Neutrophil-(NLR) and platelet-(PLR) lymphocyte ratios, C-reactive protein (CRP), haemoglobin and albumin were recorded pre- and post-operatively in each case, along with demographic and disease-specific data. Normally distributed data were compared with t-tests and expressed as mean [standard error of mean]. Non-parametric data were analysed using Mann-Whitney U tests (median [inter-quartile range]), and proportions compared with Fisher's exact test. Correlations were assessed using Pearson's correlation coefficient Results: Mean age at surgery was similar between groups (66 vs. 68 [controls] years; p=NS). Mean pre-operative PLR was significantly higher in the complication group (269.2 [22.8] vs. 186.3 [6.8]; p < 0.0001), as was the NLR (4.7 [0.5] vs. 3.2 [0.13]; p = 0.0002). The difference in post-op PLR (377.5 [33.2] vs. 297.6 [13.6]; p = 0.009) was significant, whilst a non-significant trend towards greater post-op NRL was seen in the complication group (15.6 [1.13] vs. 12.9 [0.72]; p = 0.065). Median post-op CRP was significantly higher in the complication group (127 [84–189] vs. 97 [56–139]; p = 0.012). There were no differences in pre- or post-operative albumin or haemoglobin between groups. Pre-op and post-op PLR have a better correlation (R=0.54) then NLR (R=0.36) in the complication groups. There were significantly more deaths (all causes) (7/54 [13%] vs. 7/161 [4.3%]; p = 0.049), disease-specific deaths (5/54 [9.3%] vs. 4/161 [2.5%]; p = 0.046) and disease-specific recurrence (11/54 [20.4%] vs. 14/161 [8.7%]; p = 0.028) in the complications group Conclusion: Pre-operative elevation of inflammatory cell ratios (NLR and PLR) are novel predictors of post-operative complications following surgery for rectal cancer, and may also predict poor cancer-specific outcomes. This data suggests that tumour biology holds an important influence over complications rather than technical factors alone Disclosure of interest: None Declared. References: Cook EJ, Walsh SR, et al . Int J Surg. 2007;5(1):27–30 Proctor MJ, Morrison DS, et al . Eur J Cancer 2011;47(17):2633–41